Fracture toughness of zirconia ceramic crowns made by feather-edge tooth preparation design - Mirković Nemanja; Špadijer-Gostović Aleksandra; Lazić Zoran; Trifković Branka (Vojnosanitetski Pregled)
Background/Aim. Fracture toughness determines functional crown strenght and prevents damages on ceramics during mastication. There is a lack of relevant literature data about fracture toughness of crowns made by feather-edge preparation. Mechanical testing of ceramic samples is supposed to show if feather-edge tooth preparation is a successful method for making ceramic crowns without any risk of reduction of their mechanical properties. This research was done to establish effects of feather-edge tooth preparation on fracture toughness of single zirconia ceramic crowns. Methods. The research was performed as an experimental study. Sixty (60) ceramic crowns were made on non-carious extracted human premolars. Thirty (30) crowns were made on the basis of feather-edge preparation (experimental group I). The group II included 30 crowns made on 1 mm rounded shoulder. Crowns fabrication was executed on a copy mill production system “Zirkonzahn” (Zirkonzahn GMBH, Gais, Germany). The spherical compression test was used to determine fracture toughness, using 6 mm diameter ceramic ball. Fracture load for damaging ceramic crown was recorded on a universal testing machine - Zwick, type 1464, with the speed of 0.05 mm/min. Results. The results of this research introduced significant differences between fracture toughness of ceramic samples in every examined group. However, fracture toughness of crowns from both group was above 2 000 N, what was double beyond a recommended value. The mean value of fracture toughness in the feather-edge group was 2 090 N, and in shoulder group it was 2 214 N. Conclusion. This research showed a high fracture toughness of zirconia crowns made on feather-edge preparation. The examined crowns showed a fracture resistance at a sufficient distance in relation to the minimum values of functional loads. Further research of functional loads of these crown is necessary, as well as research of marginal adaptation of cemented crowns and gingival inflammatory response.